Pengaruh Citra Merek dan Kredibilitas Influencer Terhadap Keputusan Pembelian dengan Kepercayaan Merek Sebagai Variabel Intervening pada Followers Instagram Kosmetik Emina - Putri Nadila; Juninda Rahmaida Saragih; Fitrianingsih; Bobby Hartanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Thirs study airms to derterrmirner ther Irnfluerncer of Brand Irmager and Irnfluerncerr Crerdirbirlirty on Purchasirng Dercirsirons wirth Brand Trust as an Irnterrvernirng Varirabler on Ermirna Cosmertircs Irnstagram Followerrs. Ther rerserarch merthod userd irs a quantirtatirver merthod usirng ther herlp of Smart PLS verrsiron 3.0 whirch was collercterd from ther rersults of dirstrirbutirng querstironnairrers to 100 Ermirna Cosmertircs Irnstagram Followerrs. Ther analysirs merthod userd irn thirs study irs to user an irnstrumernt terst, namerly a valirdirty and rerlirabirlirty terst. merasurermernt moderl (outerr moderl) namerly valirdirty terst, rerlirabirlirty terst, thern structural moderl (irnnerr moderl) irncludirng: coerffircirernt of derterrmirnatiron / r-squarer (r2), goodnerss of firt moderl and hypothersirs terstirng wirth t-statirstirc terst and irndirrerct erfferct terst (irndirrerct erfferct). Ther rersults of Smart PLS 3.0 irn thirs study arer that Brand Irmager has an erfferct on Brand Trust, Irnfluerncerr Crerdirbirlirty doers not haver an erfferct on Brand Trust, Brand Irmager has an erfferct on Purchasirng Dercirsirons, Irnfluerncerr Crerdirbirlirty doers not haver an erfferct on Purchasirng Dercirsirons, Brand Trust has an erfferct on Purchasirng Dercirsirons, Brand Irmager has an erfferct on Purchasirng Dercirsirons wirth Brand Trust as an Irnterrvernirng Varirabler, Irnfluerncerr Crerdirbirlirty has no erfferct on Purchasirng Dercirsirons wirth Brand Trust as an Irnterrvernirng Varirabler.